Basin‐Scale CO2 Emissions From the East River in South China: Importance of Small Rivers, Human Impacts and Monsoons. Issue 1 (10th January 2023) - Liu, Boyi; Wang, Zifeng; Tian, Mingyang; Yang, Xiankun; Chan, Chun Ngai; Chen, Shuai; Yang, Qianqian; Ran, Lishan
Abstract: Riverine carbon dioxide (CO2 ) emissions are an essential component of the riverine carbon cycle, but an accurate assessment of riverine CO2 emission fluxes is still hindered by the spatial and temporal variations among river basins caused by differences in climate, watershed characteristics, and human activity. Here, we evaluate the riverine CO2 flux from the subtropical East River Basin (ERB) in south China, a region strongly affected by monsoon climate and anthropogenic land use changes. Our results suggest small rivers are major contributors to riverine CO2 emissions, even with relatively low CO2 concentrations and small water surface areas (SAs). They contribute disproportionately to 74.4% of the total fluxes due to high gas transfer velocity ( k ) across the water‐air interface. Land use changes have substantially enhanced CO2 emissions from river networks. Normalized areal riverine CO2 fluxes in the urban‐ and cropland‐dominated Middle and Lower ERB (27.6 and 39.4 g C m −2 yr −1 ) were two and three times higher than the 9.1 g C m −2 yr −1 in the forest‐dominated Upper ERB. Due to the larger water SA and higher k caused by monsoon‐induced precipitation, the East River acts as a stronger carbon source during the wet season, emitting 0.67 Tg C yr −1 to the atmosphere, which is about twice that during the dry season (0.33 Tg C yr −1 ). Our study illustrated how monsoon climate and land use in the ERB have regulated its riverine CO2 emissions. Our findings also provided valuable insights into the role of small rivers in the basin‐wide carbon cycle. Plain Language Summary: An accurate calculation of carbon dioxide (CO2 ) emitted from rivers to the atmosphere is important for a better understanding of the carbon cycle in river basins. However, the lack of studies in some hotspots of riverine CO2 emissions has hampered the accuracy of the current estimate. Here, we evaluate the amount of riverine CO2 emitted from the subtropical East River Basin (ERB) in south China. Our results suggest that small rivers are major sources of CO2 emissions, responsible for around three‐fourths of the total emissions. Meanwhile, human‐induced land use changes have substantially enhanced CO2 emissions from rivers. Areal riverine CO2 emissions in the urban‐ and cropland‐dominated Middle and Lower ERB were two and three times higher, respectively, than that in the forest‐dominated Upper ERB. Furthermore, two‐thirds of the annual riverine CO2 emissions occurred during the wet season from April to September, implying that seasonal variation must be considered when calculating the CO2 emissions. Our study illustrated how climate and land use in the ERB have regulated its riverine CO2 emissions. The results shed light on the disproportionate role of small rivers in assessing the carbon cycle from a basin‐wide perspective. Key Points: Small rivers are major contributors of CO2 emissions despite their low CO2 concentrations and small surface areas Anthropogenic land use changes can enhance land–river carbon transport and riverine CO2 emissions Strong CO2 emissions during the wet season suggest that seasonal variation must be considered when evaluating riverine CO2 emissions